2014
DOI: 10.1186/bf03353396
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic field variations arising from the seismic dynamo effect for aftershocks of the M7.1 earthquake of 26 May 2003 off Miyagi Prefecture, NE Japan

Abstract: Some examples of electric and magnetic field variations have recently been reported by Honkura and his colleagues in association with earthquakes, and these variations have been interpreted by them in terms of the seismic dynamo effect. In order to confirm that this effect is a universal phenomenon rather than a phenomenon appearing in a special local condition, we made magnetotelluric (MT) observations above the hypocentral area of the M7.1 earthquake which occurred off Miyagi Prefecture, northeastern Japan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 7 publications
4
25
0
Order By: Relevance
“…Ujihara et al, 2004;Iyemori et al, 2005;Kotsarenko et al, 2005). Ujihara et al (2004) observed highfrequency fluctuations in the northward and eastward electric and magnetic field measurements that are similar to the seismogram readings during the aftershocks of the May 2003 earthquake in Japan using a ground-based magnetotelluric equipment.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…Ujihara et al, 2004;Iyemori et al, 2005;Kotsarenko et al, 2005). Ujihara et al (2004) observed highfrequency fluctuations in the northward and eastward electric and magnetic field measurements that are similar to the seismogram readings during the aftershocks of the May 2003 earthquake in Japan using a ground-based magnetotelluric equipment.…”
Section: Introductionsupporting
confidence: 49%
“…Ujihara et al, 2004;Iyemori et al, 2005;Kotsarenko et al, 2005). Ujihara et al (2004) observed highfrequency fluctuations in the northward and eastward electric and magnetic field measurements that are similar to the seismogram readings during the aftershocks of the May 2003 earthquake in Japan using a ground-based magnetotelluric equipment. Iyemori et al (2005) observed two geomagnetic pulsations during the 26 December 2004 Sumatra earthquake using ground-based magnetometers of Phimai in Thailand and Tong Hai in China.…”
Section: Introductionsupporting
confidence: 49%
“…Since the finding of electric and magnetic field variations due to the so-called seismic dynamo effect in the case of the 1999 Izmit earthquake in northwestern Turkey (Honkura et al, 2000, we have tried to make magnetotelluric (MT) observations on various occasions Ujihara et al, 2004). In some cases, seismic observations were also made simultaneously with MT observations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for small earthquakes, electric and magnetic signals due to the seismic dynamo effect were small and possible precursory signals should be much smaller than the noise level Ujihara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pride and Morgan, 1991;Gershenzon, 1992;Pride, 1994;Pride and Haartsen, 1996;Haartsen and Pride, 1997;Garambois and Dietrich, 2002;Huang, 2002;Ren et al, 2010a, b). Appearance of unambiguous electric field changes was mostly synchronized with the arrival of seismic wave (Yamada and Murakami, 1982;Honkura et al, 2000Mogi et al, 2000;Nagao et al, 2000;Matsushima et al, 2002;Ujihara et al, 2004). Recently we proposed a new mechanism for electric field generation by seismic wave or more specifically by ground motion, based on some observational examples (Honkura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%